Approximation operators by using finite family of reflexive relations - Abu-Donia, Hassan; Salama, Amgad (International Journal of Applied Mathematical Research, 2015)
In this paper, we generalize the two types of Yao’s lower and upper approximations, using finite number of reflexive relations. Moreover, we give a comparison between these types and study some properties.